Struktural-Fungsionalisme - Amri Marzali (Antropologi Indonesia, 2006)
This article deals with the concepts of function and social structure, developed by two leading figures in British Social Anthropology, Radcliffe -Brown and Malinowski, before the Second World War. In this article, the author distinguishes Malinowski's concept of function from Radcliffe -Brown's, delineates Radcliffe-Brown's concept of social-structure and Evans-Pritchard's review of this concept. This article particularly intends to help the Indonesia students to study anthropological theory in their own language. Key words: organic analogy; social structure; institution; ideographic method.